Advancing And Improving Algorithms for Secure and Efficient Data Transmission in Ningxia, China’s Network Environment - Yang Ziyi; Divya Midhunchakkaravarthy; Munir Kolapo Yahya-Imam (Revista Electronica de Veterinaria, 2024)
This paper is about developing and optimizing secure and efficient data transfer algorithms in Ningxia, China: a typical region by its unique geographical and technological characteristics. Today, digital infrastructure development is one of the elements to enhance the national economy of Ningxia, China, but it suffers significant challenges facing low bandwidth, latency, and increasing cyber threats. This research addresses the development of the algorithmic solutions which, beyond promoting an optimization of data transmission, ensure the integrity and confidentiality of exchanged information across the network. The design of this research is a comprehensive quantitative analysis of several algorithmic approaches; the efficiency of these algorithmic approaches in terms of latency reduction and better throughput is measured. Advanced encryption techniques and adaptive routing protocols, and their application in facilitating the transfer of secure data to meet the specific needs of that region, are made considerations. Statistical tools from SPSS are used in the data analysis, which include ANOVA, particularly the test of significance of the results obtained. Preliminary findings are indicating high correlations between better algorithms installed and increased data transmission reliability, thereby further supporting the hypothesis that algorithmic innovation has been a catalyzing factor for a resilient digital ecosystem in Ningxia, China. Further, the study would strongly highlight the need for interdependence of stakeholders, as exemplified by government agencies, local enterprise, and academic community, to ensure a beneficial environment which continues to allow greater algorithmic innovation. Ultimately, this research underlines the urgent need for investment in advanced developments in algorithms that can broadly improve the security and efficiency of data transfer and therefore support Ningxia’s growth in a more effective digitization of the Chinese economy.